Internasionalisasi Yuan: Transisi China Menuju Kekuatan Hegemon - Ramadhani, Eryan Tri (Global: Jurnal Politik Internasional, 2011)
The purpose of this research is to discover the reason why China internationalizes its currency yuan. In the realm of neorealist, state will seek ways to improve its power vis-a-vis other countries, in which this action contributes toward change in international system. One essential way is having an international currency. England and the U.S. proved the importance of pound sterling and dollar's role to underpin their hegemonic status at their time. An international status of yuan now is China's priority along with its increasing ambition to be the next hegemon, whilst the U.S. suffers its declining power particularly in economic field.